C60 intercalating Ti3C2Tx MXenes assisted by γ-cyclodextrin for electromagnetic interference shielding films with high stability. (10th November 2022) - Qian, Kunpeng; Li, Shuang; Fang, Jianhui; Yang, Yuhuan; Cao, Shaomei; Miao, Miao; Feng, Xin
Highlights: Ti3 C2 Tx MXenes intercalated with C60 assisted by γ-cyclodextrin for EMI shielding. Layer spacing increased by C60 would cause more absorption of EMWs. Antioxidative C60 would promote the durability of EMI SE. The EMI shielding films exhibit excellent mechanical robustness and flexibility. Abstract: Ti3 C2 Tx MXenes with excellent metallic conductivity and flexibility have shown a promising prospect as electromagnetic interference (EMI) shielding materials. Ultrathin, hierarchical hybrid films were fabricated by using C60 intercalating Ti3 C2 Tx MXenes with the assistance of water-soluble γ -cyclodextrin (CD). The C60 /CD complex was obtained by high-speed vibration milling using hydrophilic CD as dispersing agent. After thermal annealing treatment, the obtained hybrid film exhibited excellent EMI shielding (53.52±0.43 dB), hydrophobicity (water contact angle: 93.7°) and mechanical stability (over 0.9 million bending times). Taking advantage of the antioxidant of C60, the chemical durability of Ti3 C2 Tx MXenes based hybrid films was also improved as expected. These results indicate that the well-designed hierarchical hybrid films with the intercalation of C60 have promising potential for high-performance EMI shielding applications. Graphical abstract: Image, graphical abstract